Moral Dilemma Of Sellers In The Practice Of Manipulation Of Institutional Purchase Transaction Notes From The Perspective Of Islamic Business Ethics - Assyifa; Surya Sukti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the moral dilemma experienced by household furniture store sellers when facing requests for invoice manipulation from institutional buyers. This phenomenon is rarely discussed despite reflecting the conflict between economic interests and ethical responsibility in institutional transactions. The research aims to explain the forms of moral dilemma faced by sellers, how sellers interpret and respond to these dilemmas, and the application of Islamic business ethics principles as a resolution framework. A qualitative approach with phenomenological design was employed to understand the subjective experiences of sellers. Data were collected through semi-structured interviews and participant observation with household furniture store owners in Kecipir, Palangka Raya who serve institutional purchases. Findings reveal three patterns of invoice manipulation: price increases exceeding actual transactions, provision of blank stamped invoices, and addition of fictitious items. Sellers experience internal conflict between maintaining integrity and retaining regular customers as stable income sources. These practices violate the principles of amanah, shiddiq, justice, and tabligh in Islamic business ethics. The root cause lies in structural injustice characterized by the absence of employee compensation policies and weak internal control systems in institutions. The study concludes that strengthening spiritual awareness, establishing fair compensation policies, improving audit systems, and implementing strict sanctions are necessary to address this moral dilemma. The findings contribute to developing the concept of moral dilemma in Islamic business ethics, particularly in the context of institutional transactions that have been rarely examined previously.